De roman als wapen tegen Frankrijk: Sara Burgerhart van Wolff en Deken en de strijd tegen de ‘gallofilie’ / The Novel as a Weapon against France: Wolff’s and Deken’s Sara Burgerhart and the Struggle Against the ‘Francophilia’ - Urbaniak, Jan (Werkwinkel, 2015)
The so-called ‘moral reorientation’ (Dutch: ‘morele heroriëntatie’) was a largescale Dutch project, aimed at an improvement of ethical standards of society in the 18th century. It was also a reaction to the decay of the Dutch Republic refl ected in the literature at the end of the 18th century. Using magazines, drama’s and novels, authors provided example of a right behaviour and criticized all those phenomena, which led to a moral malaise in society. One of these phenomena was a boundless love for France, its culture, fashion, literature and philosophy. In literature it was presented as a grave danger for Dutch identity. The term ‘francophilia’ was invented. Also two Dutch female writers, Betje Wolff and Aagje Deken reacted on the dangerous symptoms of the ‘francophilia’ and warned against it in their novel Sara Burgerhart (1782). In my article I discuss some rhetorical devices, used by the authors to warn against the ‘francophilia.’ I analyse how they defi ned and further criticized this phenomenon.